AN EVALUATION OF THE STUDENT'S OPINIONS ON THE ASSOCIATE DEGREE PROGRAM IN HOME MANAGEMENT AT THE DEPARTMENT OF MANAGEMENT AND ORGANIZATION OF THEOPEN EDUCATION FACULTY AT ANADOLU UNIVERSITY - Korkmaz, Murat; Yücel, Ali Serdar; Germir, Hatice Nur; Şahbudak, Ercan; Sen, Erdal; Karta, Nurullah (My University, 2015)
This study aims to evaluate the students' opinions about their Associate Degree Program in Home Management at the Department of Management and Organization of the Open Education Faculty at Anadolu University which offers distance education. For this purpose, a questionnaire with 33 questions was conducted with the participants of the study. The study firstly presents information on the aim, function, courses and the number of students of the Associate Degree Program in Home Management, which is an education program primarily for women. Then, the study addresses the topic of women in distance education in the world and in Turkey, provides statistical data on women and men regarding education and examines the positive and negative aspects of distance education for women. 796 participants, who were selected through random sampling method, took part in the study. Data obtained through the study were analyzed and assessed through the SPSS 20.00 software. Then, Independent Samples t-Test, ANOVA, Kruskal Wallis Test and Jonckheere-Terpstra Test were used in the analysis of the data. The study concluded that the demographic characteristics of the students (age, gender, income, occupation, place of residence etc.) varied to different degrees by the reasons for choosing the program, by the courses benefited in social life, in family relationships and in working life, by the opinions about the curriculum, by the use of computer and the Internet, and by the contribution of the program to getting a vocation, to developing oneself as an individual and to raising awareness about women's rights
Keywords: Eğitim; Eğitim Araştırmaları